The role of microfinance in funding Small & Medium Enterprises: Harekello Town of Goro Dolla District in Focus, Ethiopia - Hussen, Sufiyan; Wodajo, Mengesha Robso; Tasențe, Tănase (Technium Social Sciences Journal, 2021)
This study examines the role of the Microfinance on funding of the Small and Medium Enterprises (SMEs) in Gorodola Harakallo town. This study was exploring the role of microfinance institutions on small and medium enterprise as well as the extent to which the small business have benefited from the credits scheme of microfinance institution. The specific objectives of this study were as follows; to determine at what extent role of microfinance lead to increase the volume of gross sales of participants and to understand other factors that affect SME’s growth. This study tries to answer two important questions: To what extent does microfinance lead to increase the growth of sale costumer? What are the factors that affect small and medium enterprise growth? The literature review also describes the objectives and function of MFIs, role of microfinance policy, development and policy of SMEs challenges and opportunity and relationship between MFIs and SMEs. With regard to the above objectives in mind, the research is carried out by gathering primary data through questionnaires and interviews with key informants. In addition, secondary sources of data have also been used. Eventually, using a mix of qualitative and quantitative tools, the study found out that SMEs have played positive role in improving income, creation of employment and improving the quality of life of the participants of the enterprises in the study area.